A NOVEL URINARY BIOMARKER PREDICTS 1 YEAR MORTALITY AFTER DISCHARGE FROM INTENSIVE CARE. (April 2021) - Zhang, Zhen-Yu; Nkuipou-Kenfack, Esther; Latosinska, Agnieszka; Yang, Wen-Yi; Fournier, Marie-Céline; Blet, Alice; Mujaj, Blerim; Thijs, Lutgarde; Feliot, Elodie; Gayat, Etienne; Mischak, Harald; Staessen, Jan; et al.
Abstract : Objective: The urinary proteome reflects molecular drivers of disease. The aim of this study was to construct a urinary proteomic biomarker predicting 1 year post ICU mortality. Design and method: In 1243 patients, the urinary proteome was measured on ICU admission, using capillary electrophoresis couple with mass spectrometry along with clinical variables, circulating biomarkers (BNP, hsTnT, active ADM, and NGAL) and urinary albumin. Methods included support vector modelling to construct the classifier, Cox regression, the integrated discrimination (IDI) and net reclassification (NRI) improvement and area under the curve (AUC) to assess predictive accuracy, and Proteasix and protein-proteome interactome analyses. Results: In the discovery (deaths/survivors, 70/299) and test (175/699) datasets, the new classifier ACM128, mainly consisting of collagen fragments, yielding AUCs of 0.755 (95% CI, 0.708–0.798) and 0.688 (0.656–0.719), respectively. While accounting for study site, clinical risk factors, hazard ratios in 1243 patients were 2.41 (2.00–2.91) for ACM128 (+1 SD), 1.24 (1.16–1.32) for the Charlson Comorbidity Index (+1 point), and > = 1.19 (P < = 0.022) for other biomarkers (+1 SD). ACM128 improved (P < = 0.0001) IDI (>= + 0.50), NRI (>= + 53.7) and AUC (>= + 0.037) over and beyond clinical risk indicators and other biomarkers. Interactome mapping, using parental proteins derived from sequenced peptides included in ACM128 and in-silico predicted proteases, including/excluding urinary collagen fragments (63/35 peptides), revealed as top molecular pathways protein digestion and absorption, lysosomal activity and apoptosis. Conclusions: The urinary proteomic classifier ACM128 predicts the 1-year post ICU mortality over and beyond clinical risk factors and other biomarkers and revealed molecular pathways potentially contributing to a fatal outcome.